The book market of digital distribution in Russia: trends and prospects - I. V. Lizunova (Библиосфера, 2015)
The article considers tendencies of forming the Russian book market of digital distribution in the 1990s - early XXI century. It identifies and describes main distribution channels of electronic publishing; marks forecasts of the market further development to promote the electronic content.